Perceived Barriers Of Evidence-Based Practice Among Nurses Working In Qazvin Hospitals - Mohammad Zakaria Kiaei; Mohammad Azmal; Faramarz Kalhor; Elham Shah Bahrami; Rohollah Kalhor (پیاورد سلامت, 2016)
Background and Aim: Nurses’ main tasks include the provision of healthcare services at the highest levels of quality and quantity standards, and based on the findings of scientific research. The aim of the present study is to identify and determine the barriers of evidence-based practice among nurses of Qazvin hospitals, in Iran, at 2013.